Religion and Men's Violence Against Women - Johnson, Andy J (Springer, 2015)
This reference offers the nuanced understanding and practical guidance needed to address domestic violence, sexual assault, and human trafficking in diverse religious communities. Introductory chapters sort through the complexities, from abusers' distorting of sacred texts to justifying their actions to survivors' conflicting feelings toward their faith. The core of the book surveys findings on gender violence across Christian, Jewish, Islamic, Eastern, and Indigenous traditions--both attitudes that promote abuse and spiritual resources that can be used to promote healing. Best practices are included for appropriate treatment of survivors, their children, and abusers; and for partnering with communities and clergy toward stemming violence against women.